Manifestations of the Separation and Connection of the Self in the Novel “In Search of Hope” by Ibrahim Saadi - seraiia, Yacine (El Omda in Linguistics and Discourse Analysis, 2023)
this research paper seeks to trace the manifestations of the self in its separation and connection in the novel “In Search of Amal Al-Ghabrini” by Ibrahim Saadi, which inevitably reveals those cultural, social, and political dimensions and clarifies the stage of self-aggravation manifested through functions equivalent to the factors of the personalities that frame their artistic framework through Characters (Amal Al-Ghabrini, Ounas Khadraoui called Mustafa Nuri / the stranger, Al-Mahdi Al-Maghrai called (the fugitive), Modibo Baratori...).